A Model For Analyzing the Universality and Transferability of Management - Koontz, Harold (Academy of Management Journal, 1969)
The fundamentals of management comprise elements even of an embryonic science, then they must be universal and apply in varying environments and cultures. By separating science from art, this article suggests a model by which the basics of management may be separated from non-managerial factors in determining enterprise effectiveness.